GENDER MARK OF MARGINALIZED PEOPLE (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
The adoption of the Law on Gender Equality on May 20, 2021 raised questions in the domestic public about the application of the Law. In the Law, in Art. 3 clearly states what is meant by gender equality, inter alia "equal rights, responsibilities and opportunities, (...), equal participation and balanced representation of women and men in all areas of social life, equal opportunities for the exercise of rights and freedoms". Emphasizing equal opportunities for the realization of the rights and freedoms of women and men, the author tries to draw the attention of the scientific public to the position of women and men in penal justice, in the past even in present times, in Serbia. Penal justice is dominated by retributive justice, with the possibility of applying standardized restorative justice. A basic research question is related to the need to integrate gender equality and gender perspective into the justice system, and, vice versa, seek to observe how the justice system can improve gender equality and integrates a gender perspective. The attention will also be paid to issues related to the gender perspective in the prosecution of perpetrators of criminal acts, convicts, as well as the gender approach to security. The application of the historical-legal and normative methodological procedure will be supplemented by positivist ones approach to the basic research question. The role of women activists, as well as scientists / researchers in criminology and penology, has often been neglected and relegated to the background.
Keywords: gender; equality; penal justice; restorative justice.